UNDERSTANDING AND DESCRIBING RELATIONSHIP OF STATE LAW AND HUMAN RIGHT - Hutabarat, Dany Try Hutama; Fransisca, Zenny; Ritonga, Fauziah; Pardede, Dinda Julita; Almas, Salsabila; Sikumbang, Nandra Astuti; Mutiara; Khoiriyah, Anggi; Hamizah, Siti; Malahayati; Suryadi (Transpublika Publisher, 2021)
Human rights are a natural right that a person is born with; they cannot be taken away and their existence cannot be denied; in addition, human rights serve as accolades. Human rights and the rule of law are inextricably linked, and the rule of law, of course, prioritizes and defends human rights. The function of the law itself is to safeguard humans while they pursue their varied interests, with the caveat that individuals must also consider the interests of others in their pursuit of their own interests. In addition to the protection provided by the law, we have the right to protection from the government. The existence of a state of law signifies that both the state and society acknowledge the importance of human rights protection and guaranteeing their fulfillment. It will be possible to impose the appropriate punishment if a breach of human rights occurs in this manner. It is necessary to understand the relationship between the state of law and human rights in order to prevent human rights breaches from occurring.